MENERAPKAN MODEL THINK TALK WRITE DALAM SEJARAH PERTUMBUHAN ILMU PENGETAHUAN MASA ABBASIYAH - NURHAYATI MOCHTAR (MGMP PAI Jawa Barat, 2022)
The learning system is a combination of components that are integrated and interconnected tith one another. These components include learning objectives, learning materials, methods used and evaluation tools used the end of learning. Theachers must be skilled in choosing and combining the four so that learning outcomes can satisfy both teachers and students. What learning model will be used to match the material at that time. Because the selection of an appropriate learning model will make it easier for teachers to deliver material and streamline time, is is easy for students to understand the learning material. The Think Talk Write (TTW) learning model is an effective, efficient and fun model for student in studying the History of the Growth of Science in the Abbasid Period. Think Talk Write (TTW) cooperative learning model in the History of the Growth of Science during the Abbasid Period in class VIII.B of SMP Negeri 8 Banjar can increase students’ learning activities. With the activiness of these students, learning outcomes also increase. The increase in learning outcomes can be seen from the graph of student learning outcomes from 18% up to 93%. The average value of learning outcomes also increased from 70 to 87.